2005
DOI: 10.4049/jimmunol.175.9.5966
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of Highly Homologous Killer Ig-Like Receptor Gene Alleles

Abstract: Mature human NK lymphocytes express the highly homologous killer Ig-like receptor (KIR) genes in a stochastic fashion, and KIR transcription precisely correlates with allele-specific DNA methylation. In this study, we demonstrate that CpG methylation of a minimal KIR promoter inhibited transcription. In human peripheral blood NK cells and long-term cell lines, expressed KIR genes were associated with a moderate level of acetylated histone H3 and H4 and trimethylated histone H3 lysine 4. Histone modifications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 37 publications
6
72
1
Order By: Relevance
“…29 In addition, several reports have provided convincing evidence that DNA methylation controls KIR expression. 24,30,31 Silent KIR alleles are methylated, whereas actively transcribed KIR alleles are hypo-methylated. 24,31 Although it is clear that methylation is responsible for maintaining the stable pattern of KIR expression in adult NK cells, no molecular mechanism to explain the generation of selective gene expression has emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In addition, several reports have provided convincing evidence that DNA methylation controls KIR expression. 24,30,31 Silent KIR alleles are methylated, whereas actively transcribed KIR alleles are hypo-methylated. 24,31 Although it is clear that methylation is responsible for maintaining the stable pattern of KIR expression in adult NK cells, no molecular mechanism to explain the generation of selective gene expression has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…24,30,31 Silent KIR alleles are methylated, whereas actively transcribed KIR alleles are hypo-methylated. 24,31 Although it is clear that methylation is responsible for maintaining the stable pattern of KIR expression in adult NK cells, no molecular mechanism to explain the generation of selective gene expression has emerged. An alternative model for the role of antisense transcription would be the inhibition of forward transcription from the distal KIR promoter as a result of promoter competition.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study KIR transcripts in NK92 cells, it was necessary to induce demethylation with 5-aza-2-deoxycytidine (5-aza), since the KIR2DL4 gene is the only family member expressed by this cell line, and treatment with 5-aza is required to induce expression of the other KIR genes. [8][9][10] As shown in Figure 3a, KIR3DL1 and KIR2DL2 proximal transcripts were only detected in NK92 cell RNA derived from 5-aza-treated cells. Numerous start sites of proximal transcripts were detected, consistent with previous studies performed by conducting 5'-RACE on KIR transcripts.…”
Section: Detection Of Kir Intergenic Transcriptsmentioning
confidence: 99%
“…Three separate studies observed that non-expressed KIR alleles are methylated, while treatment with the demethylating agent 5-aza-2-deoxycytidine (5-aza) resulted in the de novo expression of KIR genes. [8][9][10] How methyltransferases are recruited and what governs selective methylation is unknown, and studies have focused on the KIR promoter elements.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that histone H3 and H4 proteins are substantially acetylated at the Lys9 and Lys14 positions and H4 acetylation at the 5th, 8th, 12th, and 16th positions in both KIR3DL1+ and KIR3DL1-NK cells (Chan et al, 2005). The level of KIR3DL1-associated histone acetylation and methylation was higher in KIR3DL1+ NK cells than in KIR3DL1-NK cells; however, histone H3 methylation at Lys4 (H3K4) is only 2.6-fold higher in KIR3DL1+ NK cells than that in KIR3DL1-NK cells, although the histone H3K4 methylation levels correlated well with the KIR3DL1 promoter to lead to upregulation of KIR3DL1 gene expression, named KIR3DL1-associated histone H3K4 methylation.…”
Section: Histone Modifications Of Kirmentioning
confidence: 99%